Elevation-dependent patterns of snow-gum dieback are associated with subspecies’ trait differences and environmental variation - Bryant, Callum; Ball, Marilyn C.; Borevitz, Justin; Brookhouse, Matthew T.; Carle, Hannah; Cunningham, Pia; Davey, Mei; Davies, James; Eason, Ashleigh; Erskine, Joseph D.; Fuenzalida, Tomas I.; Grishin, Dmitry; et al. (bioRxiv, 2023)
Subalpine forests worldwide face the synergistic threats of global warming and increased biotic attack, and the collapse or transition of subalpine forests is predicted in south-eastern Australia under future climates. The recent widespread dieback of subalpine snow gum forests due to increased activity of a native wood-boring longicorn beetle suggests this process may already be underway. We investigated how variation in tree tissue traits and environmental conditions correlated with elevation-dependent spatial patterns of forest mortality. We hypothesised that increased vulnerability of subalpine snow gums to wood-borer-mediated dieback at intermediate elevations was associated with poorly-resolved differences in traits between montane (Eucalyptus pauciflora subsp. pauciflora) and subalpine (E. pauciflora subsp. niphophila) snow-gum subspecies. We first sought to characterise variation and elevation-dependent transitions in 20 structural and drought-related functional traits among 120 healthy trees distributed along a 1000m elevation transect which spanned the subspecies transition zone. Secondly, we surveyed 774 trees across 53 sites between 1280-1980m asl. to explore associations between borer-damage severity, elevation, subspecies, and a subset of traits that differed between subspecies. These snow-gum subspecies exhibited mean differences and/or divergent elevation responses in 25% of traits surveyed, indicating contrasting suites of traits between montane and subalpine subspecies. Increased borer-damage severity across the montane-to-subalpine subspecies transition was correlated with lower bark thickness, whereas reduced borer damage at the highest elevations was associated with greater precipitation and lower temperatures. Our results suggest that due to possessing distinct traits associated with increased borer susceptibility, subalpine snow-gum forests will be subject to increased risk of severe borer-mediated forest dieback under warmer and drier future climates. Identifying traits contributing to species’ distribution limits and biotic-agent vulnerability remains critical for predicting, monitoring, and possibly mitigating forest and vegetation declines under future climates.